The Influence of Social Media Addiction on Adolescent Self-Concept - Sari, Dhita Kurnia; Kartika Ayu Rachmawati; Byba Melda Suhita; Lingga Kusumawardani; Dedi Saifulah (Universitas STRADA Indonesia, 2023)
Background: The use of social media can have a good as well as a bad influence. Its bad influence, there is empirical evidence to suggest that compulsive use of social media can have an effect on a person's self-concept, especially among adolescent smartphone users. Purpose: The purpose of this study is to analyze the influence of social media addiction on the self-concept of adolescents in Kepanjen Kidul village. This study used a correlation analysis design with a cross sectional approach. The population of this study was adolescents in kepanjen kidul village who were indicated to have social media addiction of 34 people. Methods: The sampling technique in this study used simple random sampling, while the instruments used were questionnaire sheets, and statistical tests using spearmans rank. Results: The results of each variable were obtained by respondents who experienced a moderate level of social addiction as many as 16 respondents (47.1%) respondents who had a negative self-concept as many as 21 respondents (61.8%) The results of the spearmans rank statistical test obtained a cophysific value of 0.486 and p-value by 0.004 < 0.05, it can be concluded that there is an influence of social media addiction on the self-concept of adolescents in the village of kepajen kidul. Conclusion: It can be concluded that a strong relationship with a positive direction the higher the Addiction to Social Media has an impact on the higher the Negative Self-Concept experienced.